Cardiovascular disease prevention with a multidrug regimen in the developing world: a cost-effectiveness analysis - Gaziano, Thomas A (2006)
BACKGROUND: Cardiovascular disease is the leading cause of death, with 80% of cases occurring in developing countries. We therefore aimed to establish whether use of evidence-based multidrug regimens for patients at high risk for cardiovascular disease would be cost-effective in low-income and middle-income countries. METHODS: We used a Markov model to do a cost-effectiveness analysis with two combination regimens. For primary prevention, we used aspirin, a calcium-channel blocker, an angiotensin-converting-enzyme inhibitor, and a statin, and assessed them in four groups with different thresholds of absolute risks for cardiovascular disease. For secondary prevention, we assessed the same combination of drugs in one group, but substituted a β blocker for the calcium-channel blocker. To compare strategies, we report incremental cost-effectiveness ratios (ICER), in US$ per quality-adjusted life-year (QALY). FINDINGS: We recorded that preventive strategies could result in a 2-year gain in life expectancy. Across six developing World Bank regions, primary prevention yielded ICERs of US$746–890/QALY gained for patients with a 10-year absolute risk of cardiovascular disease greater than 25%, and $1039–1221/QALY gained for those with an absolute risk greater than 5%. ICERs for secondary prevention ranged from $306/QALY to $388/QALY gained. INTERPRETATION: Regimens of aspirin, two blood-pressure drugs, and a statin could halve the risk of death from cardiovascular disease in high-risk patients. This approach is cost-effective according to WHO recommendations, and is robust across several estimates of drug efficacy and of treatment cost. Developing countries should encourage the use of these inexpensive drugs that are currently available for both primary and secondary prevention.